Virus-receptor interaction in the adenovirus system: characterization of the positive cooperative binding of virions on HeLa cells. - Persson, R (1985)
The established positive cooperativity of adenovirus 2 binding to HeLa cells revealed a strong temperature dependence. The degree of cooperativity, quantified by means of Hill coefficients, progressively increased from 10 degrees C to reach a maximum level, which was maintained between 20 and 37 degrees C. On the other hand, negative cooperativity of virion attachment was apparent at 3.0 degrees C and on glutaraldehyde-stabilized cells. The corresponding monovalent ligand of the system, the fiber antigen, demonstrated only weak-positive cooperativity of the binding at 37.0 degrees C, which was absent at 3.0 degrees C. Dithiothreitol and dansylcadaverine, reagents inhibiting clustering of ligand-receptor complexes in the plasma membrane, markedly reduced the degree of positive cooperative binding at 37.0 degrees C. Evidently, the positive cooperative binding of adenovirus to HeLa cells at 37.0 degrees C is a consequence of both the multivalency of virus attachment proteins, i.e., fibers, on the virion and of the capacity of the receptor sites to migrate in the plane of the plasma membrane, forming local aggregates of virus-receptor site complexes.